Effects of feed composition on the fouling on cation-exchange membranes desalinating polymer-flooding produced water - Sosa-Fernandez, P.A.; Miedema, S.J.; Bruning, H.; Leermakers, F.A.M.; Post, J.W.; Rijnaarts, H.H.M. (Journal of colloid and interface science, 2021)
[Display omitted] Cation exchange membranes (CEMs) are subject to fouling when utilized to desalinate wastewater from the oil and gas industry, hampering their performance. The kind and extent of the fouling are most likely dependent on the composition of the stream, which in practical applications can vary significantly. Fouling experiments were performed on commercial cation exchange membranes, which were used in electrodialysis runs to desalinate solutions of varying composition. The variations included ionic strength, type of ions, amount of viscosifying polyelectrolyte (partially hydrolyzed polyacrylamide), presence of crude oil, and surfactants. Performance parameters, like electric potential and pH, were monitored during the runs, after which the membranes were recovered and analyzed. Fouling was detected on most CEMs and occurred mainly in the presence of the viscosifying polyelectrolyte. Under normal pH conditions (pH ~ 8), the polyelectrolyte fouled the concentrate side of the CEMs, as expected due to electrophoresis. However, by applying a current in the opposite direction, the polyelectrolyte layer could be removed. Precipitation occurred mostly on the opposite side of the membrane, with different morphology depending on the feed composition.